Laparoscopic D3 lymphadenectomy for right colon cancer - Cerchiari, Emilia; Lavega, Álvaro; Gabito, Isabel; Liz, Alejandra; Lapiedra, Diego; Gayo, Gonzalo; Viola, Marcelo (Cirugía del Uruguay, 2022)
Introduction ________________________________________ Colon cancer is frequent in our environment. Those located on the right colon have a worse prognosis. D3 lymphadenectomy involves resection of the central nodes, anterior to the superior mesenteric axis. Additionally, complete mesocolonic excision has been shown to improve oncological outcomes. Description ________________________________________ This is a patient in Trendelenburg position and lateralization to the left. The surgeon stands to the patient's left and the first assistant to his right. The second assistant to the right of the patient. Placement of a 10mm supraumbilical trocar for a video camera, a 12mm trocar in FII for the surgeon's right hand, and a 5mm trocar in the right hypogastrium and hypochondrium for the surgeon's left hand and for the second assistant, respectively. Surgery begins by identifying and clipping the ileo-colic pedicle. Release of the duodenum in favor of Fredet's fascia. Identification and clipping at the origin of the right branch of the middle colic pedicle, and of the venous trunk of Henle. Opening of the gastrocolic ligament. Release of the colon laterally in favor of Toldt's right fascia is completed. Visceral section and latero-lateral ileo-colic anastomosis, intracorporeal mechanics. Extraction of the piece through a median infraumbilical incision of 10cm. Conclusions ________________________________________ D3 lymphadenectomy is a feasible and safe laparoscopic surgery, to be considered in selected cases, for locoregional control of advanced right colon tumors. View the video at: https://www.youtube.com/watch?v=_gegDKDZjew